miR‐132 loss de‐represses ITPKB and aggravates amyloid and TAU pathology in Alzheimer's brain - Salta, Evgenia (EMBO Mol Med, 2016)
microRNA‐132 (miR‐132) is involved in prosurvival, anti‐inflammatory and memory‐promoting functions in the nervous system and has been found consistently downregulated in Alzheimer's disease (AD). Whether and how miR‐132 deficiency impacts AD pathology remains, however, unaddressed. We show here that miR‐132 loss exacerbates both amyloid and TAU pathology via inositol 1,4,5‐trisphosphate 3‐kinase B (ITPKB) upregulation in an AD mouse model. This leads to increased ERK1/2 and BACE1 activity and elevated TAU phosphorylation. We confirm downregulation of miR‐132 and upregulation of ITPKB in three distinct human AD patient cohorts, indicating the pathological relevance of this pathway in AD.